Fiscal policy and the economics of financial balances - Gennaro Zezza (Levy Economics Institute of Bard College, 2009)
This paper presents the main features of the macroeconomic model being used at The Levy Economics Institute of Bard College, which has proven to be a useful tool in tracking the current financial and economic crisis. We investigate the connections of the model to the New Cambridge approach, and discuss other recent approaches to the evolution of financial balances for all sectors of the economy. We will finally show the effects of fiscal policy in the model, and its implications for the proposed fiscal stimulus on the U.S. economy. We show that the New Cambridge hypothesis, which claimed that the private sector financial balance would be stable relative to income in the short run, does not hold for the short term in our model, but it does hold for the medium/long term. This implies that the major impact of the fiscal stimulus in the long run will be on the external imbalance, unless other measures are taken.
Keywords: E12; E17; E21; 330; Fiscal policy; financial balances; New Cambridge